2022
DOI: 10.3389/fcimb.2022.940847
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O88 induces intestinal damage and inflammatory response through the oxidative phosphorylation and ribosome pathway in Pekin ducks

Abstract: Colibacillosis is one of the major health threats in the poultry industry worldwide. Understanding the pathogenic mechanisms involved in Escherichia coli-induced inflammatory response may lead to the development of new therapies to combat the disease. To address this, a total of 96 1-day-old male lean Pekin ducklings were employed and randomly allocated to two treatments, each with six replicates of eight ducks. Ducks in the experiment group (EG) and the control group (CG) were separately orally administered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The heterophils are the fastest to E. coli within 6 hours postinfection response, contributing to the clearance mechanism by degranulation and antibacterial compounds (Mol et al, 2019). Besides, the macrophage is a key component to contribute to tissue self-repair inflammation (Li et al, 2022). Thus, when there is either a localized or systemic infection, the organ will be changed functionally, resulting in poor performance of the chicken.…”
Section: Discussionmentioning
confidence: 99%
“…The heterophils are the fastest to E. coli within 6 hours postinfection response, contributing to the clearance mechanism by degranulation and antibacterial compounds (Mol et al, 2019). Besides, the macrophage is a key component to contribute to tissue self-repair inflammation (Li et al, 2022). Thus, when there is either a localized or systemic infection, the organ will be changed functionally, resulting in poor performance of the chicken.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that E. coli infection can damage the intestinal barrier and trigger mucosal inflammatory responses subsequently in ducks, which is an energy-consuming process [ 58 ]. In the previous study, ducks infected with E. coli impaired the growth performance of ducks through an interfering energy metabolism pathway, down-regulating gene expression related to the ribosome and oxidative phosphorylation [ 59 ]. In the present study, B. subtilis reduced intestinal oxidative stress through interfering with ribosome and energy metabolism by up-regulating the expression of genes that encode mitochondrial ribosome proteins, ribosome biogenesis and translation factors.…”
Section: Discussionmentioning
confidence: 99%